Sistem Pakar Dengan Metode Backward Chaining Untuk Pengujian Transistor Di Laboratorium Elektronika - Jhonson Efendi Hutagalung; Jeperson Hutahaean (RJOCS (Riau Journal of Computer Science), 2015)
The expert system is an artificial intelligence, expert systems is a program to store and process knowledge for a particular area, that's why they were able to answer questions and solve problems, according to the consensus of the experts. Backward Chainning models in reverse of the hypothesis, a potential or conclusion which must be proved by the facts that support the hypothesis.Backward Chainning also well described in the form of reasoning began with the goal to the subgoal reach the goal of understanding means fulfilling subgoal. Decision tree is the result of a tracking process that can be used to explain the answer to the question of questions. Chainning Backward algorithm uses primary data structure in the formation of the decision tree. In the knowledge base necessary rules which will be stored in the database. For the rules on the formation of the expert system can be made based on the facts mentioned above. To rule pin test rules that generate multimeter to measure the use of transistors is right and wrong. Read the scale rule is a rule of the final results of the test transistors are good, leaking or broken so it can not be used anymore